Investigation of a miRNA-Induced Gene Silencing Technique in Petunia Reveals Alterations in miR173 Precursor Processing and the Accumulation of Secondary siRNAs from Endogenous Genes. - Yao Han; Bin Zhang; Xiaoting Qin; Mingyang Li; Yulong Guo (PLoS ONE, 2015)
MIGS (miRNA-induced gene silencing) is a straightforward and efficient gene silencing technique in Arabidopsis. It works by exploiting miR173 to trigger the production of phasiRNAs (phased small interfering RNAs). MIGS can be used in plant species other than Arabidopsis by co-expression of miR173 and target gene fragments fused to an upstream miR173 target site. However, the efficiency and technical mechanisms have not been thoroughly investigated in other plants. In this work, two vectors, pMIGS-chs and pMIGS-pds, were constructed and transformed into petunia plants. The transgenic plants showed CHS (chalcone synthase) and PDS (phytoene desaturase) gene-silencing phenotypes respectively, indicating that MIGS functions in petunia. MIGS-chs plants were used to investigate the mechanisms of this technique in petunia. Results of 5'- RACE showed that the miR173 target site was cleaved at the expected position and that endogenous CHS genes were cut at multiple positions. Small RNA deep sequencing analysis showed that the processing of Arabidopsis miR173 precursors in MIGS-chs transgenic petunia plants did not occur in exactly the same way as in Arabidopsis, suggesting differences in the machinery of miRNA processing between plant species. Small RNAs in-phase with the miR173 cleavage register were produced immediately downstream from the cleavage site and out-of-phase small RNAs were accumulated at relatively high levels from processing cycle 5 onwards. Secondary siRNAs were generated from multiple sites of endogenous CHS-A and CHS-J genes, indicating that miR173 cleavage induced siRNAs have the same ability to initiate siRNA transitivity as the siRNAs functioning in co-suppression and hpRNA silencing. On account of the simplicity of vector construction and the transitive amplification of signals from endogenous transcripts, MIGS is a good alternative gene silencing method for plants, especially for silencing a cluster of homologous genes with redundant functions.